Isolation of a thioesterase gene from the metagenome of a mountain peak, Apharwat, in the northwestern Himalayas - Sudan, Avneet Kour (Springer Berlin Heidelberg, 2012)
The soil metagenome of Apharwat (latitude 34.209° and longitude 74.368°) was explored for the presence of esterase encoding genes using a cultivation-independent approach, metagenomics. Among the various protocols tested, the method developed by Wechter was found to be the best for metagenome isolation from the soil under investigation. The purity of the isolated metagenomic DNA was not suitable for gene cloning. To improve the yield and purity of isolated metagenomic DNA, isothermal amplification of the isolated metagenomic DNA using phi (φ) polymerase in a strand displacement technique was performed. The amplified DNA was comparatively pure and the yield increased 50-fold. A metagenomic library was constructed in Escherichia coli (DH5α) using pUC19 as a vector with an average insert size ranging between 2 and 5 kb. Out of 10,000 clones generated, one clone carrying a ~1,870-bp insert hydrolysed tributyrin, indicating esterase activity. Sequence analysis revealed that the insert harboured three open reading frames (ORFs), of which ORF 3 encoded the esterase. Open reading frame 3 comprises 1,178 bp and encodes a putative 392 amino acid protein whose size correlates with most of the bacterial esterases. The esterase isolated in the present study is suggested to be a 4-methyl-3-oxoadipyl-CoA thioesterase (Accession No. JN717164.1), as it shows 60 % sequence similarity to the thioesterase gene of Pseudomonas reinekei (Accession No. ACZ63623.1) by BLAST, ClustalX and ClustalW analysis.